Factors influencing land use changes in urban areas: The case of land development projects in Ilemela Municipal Council - Marwa, Julius (Mzumbe University, 2023)
A dissertation submitted to the Department of Economics in partial/fulfilment of the requirements for the award of the degree of Project Planning and Management (MSc PPM) of Mzumbe University, Tanzania.